CODESRIA Bulletin Online, No. 3, February 2024 - A Polycentric World Will Be Possible Only with the Intervention of the ‘Sixth Great Power’ - Paris Yeros (CODESRIA Bulletin, 2024)
The collective imperialism of the US-EU-Japan triad evolved after the Second World War under the aegis of the United States, to give strategic coherence to the expansion of monopoly capitalism against the socialist East and the emerging South. Its objective was to confront the unprecedented resistance to monopoly capitalism presented by both the Soviet system, which had emerged victorious against Nazism, and the Third World, which was on the path of decolonisation. This contradiction was the essence of the systemic rivalry of the Cold War. Its origins lie precisely in the two great anti-imperialist events of the twentieth century: socialist revolution and general decolonisation. It is said that the postwar period created a ‘bipolar’ system between East and West. In fact, the conflict was much greater. It consisted of a systemic contradiction between imperialism and all anti-imperialist forces, not just deriving from the East. What is more, in this contradiction, the essence of the conflict, even between East and West, soon came to revolve around the forces of national liberation of the peoples of the Third World. That is, national liberation struggles became the principal driving force of postwar systemic rivalry. They found in the Soviet Union a systemic counterweight to imperialism, if not direct support, while the East–West conflict itself gained its dynamism in the liberation struggles of the peripheries. It is no coincidence that the biggest nuclear confrontation of the Cold War took place on account of the Cuban Revolution. It also said that the West ‘won’ the Cold War. In the 1990s, neoliberals in their euphoria even postulated the ‘end of history’, while their ‘realist’ alter egos contemplated the ways and means of consolidating a ‘unipolar’ world. One of their achievements was to impose their terms on our debate, spreading not only neoliberal and culturalist theories but also theories of ‘polarity’ and ‘geopolitics’, among others, borrowed from North American political science, unrelated to the theory of imperialism of the Marxist-Leninist tradition. This present intervention seeks to provide some clarification regarding these concepts. It is true that the terms of polarity today have already been appropriated by anti-imperialist forces to occupy a central place in our reflections. However, there is still need for clarification and adaptation, if we are to persist in using such concepts, given that in their original form they are distant from our purposes. Above all, the analytical emphasis on ‘great powers’ diverts the focus from what Marx called the ‘Sixth Great Power’, people’s revolutionary power. Nor do these concepts clarify the challenges of global development that confront the peripheral countries, which today, more than ever before, require that their external economic relations be subordinated to the power of popular sovereignty. The most accurate term for the coveted transition, in our view, would be ‘polycentrism’. It postulates a multiplicity of centres in which countries and regions of the South are able to pursue paths of sovereign and popular development—that is, ‘delink’ from the law of value dominated by imperialism.2 But, after all, whatever the terminological preference, what really matters is the content of the analysis. Who Won the Cold War? The theory of polarity survived into the post-Cold War period to contemplate a ‘unipolar moment’. Yet, it is not possible to maintain that in that transition there was a clear victory for the West. Monopoly capitalism did not emerge from the Cold War unscathed. In the mid-1960s it was already in permanent crisis, as a result of its own contradictory logic and, above all, its conflict with the East and the South. The West came out of the Cold War gravely injured. What happened from the 1970s onwards was a retrograde attempt to rescue imperialist domination. Financialisation, re-dollarisation via the oil market, new waves of capital exports, military escalation and technological leaps relaunched collective imperialism. Certainly, this revenge pushed the Soviet system beyond its limits and at the same time consolidated the neocolonial transition of the countries of the South. It would be more appropriate to see in this late phase of neocolonialism a long impasse in the systemic transition. For the fundamental contradictions of monopoly capitalism were never resolved; and financialisation, capital exports and militarisation, despite the technological leaps involved, have all become elements of a secular decline. Thus, the net balance was not entirely in favour of imperialism. Despite sealing the neocolonial transition in most of the Third World, with the notable exception of China, the relaunch of collective imperialism did not reverse decolonisation. That is, it failed to knock down the generalised system of national sovereignty achieved by the peoples of the Third World with the help of the Soviet Union. Even after almost half a century of neoliberalism, the regime has not been suppressed or overcome. There is certainly a degradation of the national sovereignty regime on the peripheries. It results from constant imperialist aggression and deep social polarisation, especially manifest in the gigantic growth of labour reserves, generating neofascist forces within countries and even leading to new semicolonial situations in a series of countries that have succumbed to imperialist invasion and territorial fragmentation. However, it is worth emphasising again that the general regime of national sovereignty has not been overthrown to this day, and this is a sacrosanct victory for the peoples of the South. Nor did the end of the Cold War put an end to the communist movement, despite the collapse and dismemberment of the Soviet Union. The communist movement retreated, but it also underwent transformations to the point of making a spectacular economic leap, especially in China, and stimulating important innovations in Cuba under the weight of the economic blockade. The obvious question may be put again: Is it still possible to say today that the West won the Cold War? It would be more accurate to say that the impasse of late neocolonialism is being undermined by the renewed advance of anti-imperialist forces, which this time around find a systemic counterweight in China itself. Even today, an analytical focus on ‘great powers’ is not justified. On the one hand, nationalism on the peripheries has been radicalising; on the other, China’s trajectory remains closely linked to the Third World. The future of China itself will depend on the character of this relationship. Throughout this systemic impasse, the transatlantic alliance maintained its effective cohesion and its insistence on expansionism and aggression, given that NATO’s sole purpose has always been the destruction of the obstacles to monopoly capitalism. The alliance expanded its operations into Africa and Asia, devoured Eastern Europe and continued to threaten the dismemberment of Russia. But internally, the same monopolistic logic, once financialised and generalised, caused wages to stagnate and eroded the policy of full employment, undoing the social pacts and the material pillars of the social democratic experiment. Under such conditions, the return to fascism was a matter of time, on both sides of the Atlantic. There are even those who believed that neofascism would create a crisis in NATO itself, that the arrival of Trump would put its liberal essence in check! But liberalism was never NATO’s raison d’être; rather, it was the generalisation of monopoly capitalism. The Resumption of the Cold War The systemic contradictions that led to the long impasse of late neocolonialism are now intensifying. If the emergence of China is the force that most took advantage of the decline of collective imperialism and undermined the economic infrastructure of the neocolonial system, NATO’s violent confrontation with Russia in Ukraine and the genocide in Palestine constitute a turning point. Russia, as the main heir to the Soviet Union—integrating a large part of its territory, its people and its memory, and benefiting from its technological capacity, energy resources and nuclear energy—continued to present obstacles to NATO’s expansionism. The focus of the dispute returned to Ukraine, which has always had superior strategic value in the designs of NATO, as in those of the Nazi army before it. Ukraine’s transformation into the spearhead of imperialism was a matter of time. NATO’s instrumentalisation of Ukraine was anything but an exercise in sovereignty. National sovereignty is, above all, an anti-imperialist formula for the exercise of popular power. The instrumentalisation of Ukraine through a coup, the promotion of neo-Nazi forces in the state apparatus, its tutelage by the NATO military apparatus and the launch of a war against Russian ethnic minorities in the east of the country, in Donbas, was an act of liquidation of sovereignty. Ukraine plunged into a simulated semicolonial situation, without being directly occupied and divided, but nevertheless was reprogrammed to launch a war against itself and to point weapons at Russia. In such a situation, any attempt to incorporate the country into NATO, with troops and missiles on the border, was obviously a casus belli for Russia. Russia had the right to intervene. The intervention was carried out against a consolidated NATO–neo-Nazi axis. Over the past two years, a horrific war has been fought at the expense of the Ukrainian people and the youth on both sides recruited in the war effort. Far from its supposed liberal ideals, NATO has shown once again that it has no qualms about supporting Nazi forces outside its borders, whatever the cost, and sponsoring wars overseas, by systematically upping the stakes with ever-increasing budgetary allocations and transfers of heavy weaponry to Ukraine. NATO also doubled the size of its land border with Russia following Finland’s entry into the alliance in April 2023. An extensive front against Russia has taken shape once again, with a supremacist ideology. NATO’s capacity for provocation and escalation of conflict is always a given, even if there is currently evident exhaustion with the war. It should be added that this war is also a tragic warning about what happens when a more vulnerable country is unable to sustain a policy of positive non-alignment towards states that are more capable of defending their strategic interests. After all, this was the most important historic lesson of the Bandung Movement: the reason for non-alignment was precisely the preservation of smaller states against their own incineration in a fight between the larger powers. If this war in Ukraine is an extension of the East-West dimension of the Cold War, the war in Palestine, which broke out again in October 2023, is the essence of the same enduring North- South conflict. This is a classic situation of settler colonialism sponsored by imperialism, one of the last unresolved colonial questions of the last century and the most consequential for the systemic transition in the twenty-first. The Zionist state has never stopped fulfilling its essential functions, which have been to dominate the peoples of the region, degrade their sovereignty and control energy resources and trade routes. The ongoing genocide against the Palestinian people is clear proof of the barbarism of the collective imperialism led by the United States and the fascist nature of its strategic designs. We are witnessing a declared ethnic cleansing of a people under occupation, perpetrated by the Zionist state and supported by the United States, the United Kingdom and the European Union. By the beginning of January 2024, at the time of South Africa’s recourse to the International Court of Justice for the crime of genocide, more than 23,000 Palestinians had lost their lives in the three months since the insurrection of 7 October (70% being women and children), over 50,000 had sustained injuries in the bombings, and another 7,000 had disappeared under the rubble. If there was still any doubt about the civilisational character of the West, it has turned to dust in the bombings of Gaza. This tragedy is also a demonstration of how the so-called ‘multipolar transition’ will evolve from now on: while the semi-peripheral powers seek to play in all directions on the global chessboard, in a new phenomenon of ‘multi-alignment’, the working people of the Third World, trapped and asphyxiated in labour reserves, will rebel and force the systemic transition forward. It should be added that the only possibility of cracks appearing within NATO is the implosion of one or more of its member governments under popular pressure. We cannot rule out this possibility in our time, although the proletariat in the West still lacks organisation and historical consciousness. But the neoliberal-neofascist dynamic directed by the monopolies inside national arenas has long taken over the entire region and set it on a path of decline and social polarisation, which will also fuel revolts. Moreover, the marginalisation of immigrant communities of African and Asian origin adds a crucial factor in driving the revolts. The recent massive demonstrations against the Palestinian genocide have in many cases propelled racially oppressed communities to the forefront of the political dynamic. These fissures will deepen. The exact ideological colouring of any cracks remains unpredictable, and we know that fascism pounces at every turn of events. But in the twenty-first century the course of this dispute is no longer predetermined. Challenges of Systemic Transition The fissures at the world level are more mature. The infrastructure of neocolonial rule is buckling under the weight of the permanent crisis of imperialism and the emergence of China. In the last twenty years, the world economy has moved to an entirely new pattern of trade, mediated today by China, this being the main trading partner of the vast majority of countries in the world. China is also a huge source of finance, which the West itself absorbs to sustain itself. The role of economic resistance on the part of Russia is also notable at this juncture. In addition to blocking NATO’s military advance, it has successfully confronted the unilateral sanctions regime, safeguarding its currency and establishing new trade partnerships. Furthermore, the heavy sanctions imposed on Russia and the freezing of 300 billion of its dollar reserves has reinforced Russia’s convergence with China and Iran. Such a strategic partnership today presents new possibilities for economic transactions and the trade of oil outside the dollar and Wall Street—that is, outside the operational mechanisms of the unilateral sanctions regime. The cracks promise increasingly to expand the space for manoeuvre for the Third World and even for popular revolts. However, a caveat is in order: except for sudden financial collapse in Wall Street, which also cannot be ruled out given the degree of debt, the road to an alternative monetary and financial system remains long. This applies to the BRICS (Brazil, Russia, India, China, South Africa) initiative, led by China, which theoretically has the potential to shift further the correlation of forces. But the future of BRICS will depend on the degree of cohesion among a group of countries whose political systems, for the most part, remain unpredictable or unreliable in strategic terms, and which simultaneously maintain close economic and/or military relations with imperialism, in this phase of ‘multi-alignment’. Their international postures still lack the necessary conviction to sustain a robust advance against the economic structures of neocolonial domination. This is the case for most BRICS members. If judged by the neocolonial structure still in force in this phase of imperialism, the new polycentric world—commonly called ‘multipolar’—has not yet taken shape, even though it is on its way. Whatever the terminological convenience, it is worth emphasising that the term ‘polycentrism’ concerns not only the distribution of a set of military, economic and other capabilities but also the ability of countries and regions to disconnect from the world law of value dominated by imperialism and build a path of autocentred, sovereign and popular development. The construction of a polycentric world, in the terms stated here, presupposes a more precise assessment of the set of challenges that prevail in this permanent crisis. In the terms put here, the systemic transition remains in its infancy, and the principal contradiction remains the same between imperialism and the working people of the Third World. However, the main contradiction has acquired new contours as the crisis of monopoly capitalism continues to deepen, consisting of the following six elements. The massive expansion of labour reserves in the world economy and their concentration in the system’s peripheries, configuring historically distinct and enduring social formations that present unprecedented challenges as a result of the severity of the crisis of social reproduction that convulses working people; The concentration and, at the same time, increasingly tighter absorption of peripheral bourgeoisies in global value systems under the command of monopoly capital, although with shifts in commercial orientations towards China and, in some contexts, through the process of anti-imperialist radicalisation and unilateral sanctions, the emergence of patriotic bourgeois fractions associated with state incentives (China, Russia, Iran, Yemen, Zimbabwe, Venezuela, etc.); The emergence of China in the triad’s own economic terrain—that is, in trade, finance and technology and the economic integration of the whole world into China’s trajectory; The acceleration of global warming and extreme and especially catastrophic climate phenomena in the tropics, precisely where labour reserves are concentrated; The inauguration of a long era marked by permanent insurrectionary pressures that emanate from the already deep social polarisation where labour reserves are once again concentrated; The widespread military escalation of the West, expanding its military presence around the world, articulating new alliances and reaching a new level of hostilities, even setting up a confrontation on the borders of a UN Security Council member and now promoting, without any moral constraint, a genocide against the Palestinian people. If polycentrism is not consolidated in time, what is really on the agenda of the twenty-first century is serial genocide against the working peoples of Africa, Asia, Latin America and the Caribbean, who are facing an existential crisis. There is no Transition Other than to Socialism The construction of a polycentric world, which will certainly be a long road, implies above all the construction of socialism itself. And in this construction it would be obvious to look to China and its leadership. However, the limits of China itself need to be analysed, especially in the context of the intensifying systemic contradiction. On the one hand, China has leveraged institutional innovations in its central planning system, which have shielded it from the worst effects of the worldwide law of value, creating conditions for its own development path. Despite extensive concessions to capitalism, it is the country that has navigated the challenges of economic transformation with more clarity, innovation and agility, without giving up the substantive gains of the 1949 revolution, especially in its agrarian question. Also, it has demonstrated that capitalism can function for the benefit of the people on the peripheries only under the control of a revolutionary force, which the Communist Party embodies. After all, this was always the meaning of socialist primitive accumulation. However, one of the biggest questions facing this unique socialist trajectory is the future of its economic relations with the peripheries. As a new round of primitive socialist accumulation has occurred, it today has a global dimension unlike anything we have seen before. It is worth recalling that the Soviet Union did not have substantive economic relations with most of the Third World, with the notable exceptions of India, China and Egypt for a time, and Cuba until the end. The path that this new world economic relationship will take is crucial for the polycentric transition. The most that can be expected from China is that it continues to circulate surpluses via the Belt and Road Initiative, that it builds new and modern infrastructure, that it shares advanced technologies, and that it plants seeds for peripheral industrialisation. But none of this will be enough to meet the challenges facing the Third World today. China will not displace the worldwide law of value to the point of favouring widespread capitalist peripheral industrialisation, nor will it suppress the law of value outside its borders by producing public utilities at the level of the current crisis of social reproduction. In the current conditions, the polycentric transition will not depend on China but on us, on our insurgency, on our abilities to change the correlation of forces. Salvation does not come from outside—just as it did not come from outside in the Cold War of the last century. Taking the path of polycentrism means very concrete things: absorbing the enormous labour reserves concentrated in the Third World into decent working and living conditions; stabilising and balancing, economically, socially and politically, rural–urban relations by means of radical agrarian reforms; planning for sovereign industrialisation, both rural and urban, without fear of dismantling and recomposing production systems; and confronting climate change at different levels of action but especially through new forms of socialist property to establish a new relationship between economy and nature. Changing power relations on a national and regional scale on the peripheries remains crucial to the overall systemic transition. And the deadline is no less urgent: the transition must occur, substantively, by the middle of the twenty-first century, if the catastrophic growth of labour reserves and the worst consequences of global warming are to be avoided. Is there any other measure of the transition to polycentrism if not through the transition to socialism? The world already finds itself in a pre-revolutionary situation, under permanent insurrectionary pressure on the peripheries, which can no longer be ignored. It is worth remembering, in this sense, Marx’s words at a time when ‘five great powers’ competed for power on the European continent and overseas. What really matters, Marx (1953) affirmed, is the ‘sixth great power’. In his words, written in February 1854: […] we must not forget that there is a sixth power in Europe, which at given moments asserts its supremacy over the whole of the five so-called ‘great’ powers, and makes them tremble, every one of them. That power is the Revolution. Long silent and retired, it is now again called to action by the commercial crisis and by the scarcity of food. <Notes> 1 Network. It was presented at the conference on Contemporary Popular Movements in India: Challenges, Prospects and Solidarities, Jawaharlal Nehru University, New Delhi, 9 June 2023; at the Training Course of the Union of Socialist Youth in the debate on The New Global Order, the Climate Emergency and Socialism in the World–Is Marxism Still Relevant?, Itapecerica da Serra (São Paulo), 6 December 2023; and the SMAIAS-ASN Summer School on ‘Rural and Urban Industrialization: Towards a Great Leap Forward’, Harare, 5-9 February 2024. I thank the participants for their comments. A fuller version will appear in Agrarian South: Journal of Political Economy, Vol. 13, No. 1, 2024. The contribution here is dedicated to CODESRIA on its fiftieth anniversary. 2 linking’ were elaborated by Samir Amin, on the basis of the revolutionary experiences of the twentieth century; see Amin (1980, 1987, 1990)